Pelatihan Aplikasi Hand Craft Untuk Nasyiatul Aisyiyah - Debby Ummul Hidayah; Masyruri Rizka Maulana; Puji Lestari (Universitas Hamzanwadi, 2022)
Improving technological competence in an organization can be done in various ways. One of them can be done by conducting training on the technology. Like the Rabak Branch of the Nasyiatul 'Aisyiyah organization, related technology training, until now, is still rarely done. One of the activities that technological tools can support is making handicrafts. However, the activity of making handicrafts is still done traditionally. Often do not arrive at the expected result. This condition makes the activity of making handicrafts not optimal. Even the modules used are usually unavailable, so each member of Nasyiatul 'Aisyiyah cannot finish making these handicrafts after the activity. Therefore, this community service activity aims to introduce android-based technology in the form of handicraft applications and to help Nasyiatul 'Aisyiyah members make handicrafts. The implementation methods in this community service activity include giving lectures explaining handcraft applications, assisting participants, and direct practice using handcraft applications. The activity is carried out offline, which is located in Bustanul Athfal 'Aisyiyah Rabak. The steps in this community service activity start from preparation, implementation, and evaluation. The implementation of this community service activity indicates that the handcraft application training activities are included in good criteria, with the evaluation value from the results of the questionnaire calculation showing the figure of 79.58%. This shows that most of the participants have been able to understand and use handcraft applications in making handicrafts